Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1365-2982.2012.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid high‐amplitude circumferential slow wave propagation during normal gastric pacemaking and dysrhythmias

Abstract: Background Gastric slow waves propagate aborally as rings of excitation. Circumferential propagation does not normally occur, except at the pacemaker region. We hypothesized that: i) the unexplained high-velocity, high-amplitude activity associated with the pacemaker region is a consequence of circumferential propagation; ii) rapid, high-amplitude circumferential propagation emerges during gastric dysrhythmias; iii) the driving network conductance might switch between ICC-MP and circular ICC-IM during circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 37 publications
(135 reference statements)
6
108
0
Order By: Relevance
“…Particularly, external electrical stimulations could also be studied, as stretch-induced contractions, blocking the neural activity to better identify the role of ICCs in modulating the contractile response to cooling. Moreover, in vitro tissue studies have demonstrated that some inflammatory mediators, especially prostaglandins, can modulate the frequency of contractions in the stomach (50,73); for this reason, use of selective inhibitors would help to better explore the mechanism responsible for the cooling contractile response of smooth muscle tissue. An extended data set for a wider range of thermal conditions would also help to unveil the contractile response of longitudinal-and circular-oriented human colonic strips.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, external electrical stimulations could also be studied, as stretch-induced contractions, blocking the neural activity to better identify the role of ICCs in modulating the contractile response to cooling. Moreover, in vitro tissue studies have demonstrated that some inflammatory mediators, especially prostaglandins, can modulate the frequency of contractions in the stomach (50,73); for this reason, use of selective inhibitors would help to better explore the mechanism responsible for the cooling contractile response of smooth muscle tissue. An extended data set for a wider range of thermal conditions would also help to unveil the contractile response of longitudinal-and circular-oriented human colonic strips.…”
Section: Discussionmentioning
confidence: 99%
“…metric potential physiological relevance density measures the ICC network volume, reflecting the amount of bioelectrical current generated thickness measures the width of cellular structures within the ICC network, which may impact electrical activity propagation through the network hole size reflects the distribution of ICC throughout the tissue (i.e. the 'tightness' of the network), and may relate to the uniformity of SMC activation contact ratio indicates the availability of conduction pathways from ICC to non-ICC regions within the MP, which may (through field coupling conduction mechanism [32]) relate to the efficiency of pacemaker activity conduction into SMC connectivity reflects the structural integrity of the ICC network, indicating the cohesion of entrainment pathways [33] anisotropy indicates the degree of preferential alignment of ICC structures, and may reflect the dominant slow wave propagation direction, potentially affecting predilection and resilience to dysrhythmia [34] rsif.royalsocietypublishing.org J R Soc Interface 10: 20130421…”
Section: Discussionmentioning
confidence: 99%
“…10 Wavefronts spread out rapidly and circumferentially from the pacemaker, however, by the mid-corpus, complete rings of activation have formed such that the rapid circumferential conduction ceases, and the rings thereafter move slowly and longitudinally down the stomach (Figure 1B). 11,13 Importantly, during gastric arrhythmias, rapid circumferential propagation re-emerges to become a major determinant of conduction patterns, as a consequence of either ectopic pacemaking or disruption to the normal ring wavefronts by conduction blocks (Figure 2). 10,13 …”
Section: The Human ‘Gastric Conduction System’mentioning
confidence: 99%
“…11,13 Importantly, during gastric arrhythmias, rapid circumferential propagation re-emerges to become a major determinant of conduction patterns, as a consequence of either ectopic pacemaking or disruption to the normal ring wavefronts by conduction blocks (Figure 2). 10,13 …”
Section: The Human ‘Gastric Conduction System’mentioning
confidence: 99%